2001
DOI: 10.1055/s-2001-15813
|View full text |Cite
|
Sign up to set email alerts
|

Cardanols from Leaves of Rhus thyrsiflora

Abstract: A mixture of 3-substituted alkyl- and alkenylphenols including nine new compounds (cardanols) was isolated from leaves of the Yemenian plant Rhus thyrsiflora (Anacardiaceae) and identified by GC-MS. The position of the double bond in the compounds bearing a monolefinic side chain was determined by their typical MS fragmentation patterns after hydroxylation and trimethylsilylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…to hypothesize that peak 9 could be 3-(8,11-pentadecadienyl) phenol (Paramashivappa et al, 2001;Phani Kumar et al, 2002;Strocchi & Lercker, 1979) and peak 12 could be 3-(10,14-heptadecadienyl) phenol. The composition of the pistachio cardanols is very different from other plant species: usually, only four compounds are found in cashew, all with a C-15 alkyl chain (Paramashivappa et al, 2001;Phani Kumar et al, 2002;Strocchi & Lercker, 1979;Tyman et al, 1981); two C-15 cardanols are reported in Semecarpus vitiensis (Pramono et al, 1985), C-15 and C-17 in Rhus vernicifera, an Anacardiacea (Du, 1990), a C-11 and a C-13 in Knema hookeriana (Alen et al, 2000), a C-15 and two C-17 in Ginkgo biloba (Tan et al, 2001) and nine different compounds in another Anacardiacea, Rhus thyrsiflora (Franke et al, 2001).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…to hypothesize that peak 9 could be 3-(8,11-pentadecadienyl) phenol (Paramashivappa et al, 2001;Phani Kumar et al, 2002;Strocchi & Lercker, 1979) and peak 12 could be 3-(10,14-heptadecadienyl) phenol. The composition of the pistachio cardanols is very different from other plant species: usually, only four compounds are found in cashew, all with a C-15 alkyl chain (Paramashivappa et al, 2001;Phani Kumar et al, 2002;Strocchi & Lercker, 1979;Tyman et al, 1981); two C-15 cardanols are reported in Semecarpus vitiensis (Pramono et al, 1985), C-15 and C-17 in Rhus vernicifera, an Anacardiacea (Du, 1990), a C-11 and a C-13 in Knema hookeriana (Alen et al, 2000), a C-15 and two C-17 in Ginkgo biloba (Tan et al, 2001) and nine different compounds in another Anacardiacea, Rhus thyrsiflora (Franke et al, 2001).…”
Section: Resultsmentioning
confidence: 94%
“…The cardanols were also found in other vegetable species (Alen et al, 2000;Du, 1990;Franke, Masaoud, & Schmidt, 2001;Pramono, Gleye, Moulis, Debray, & Stanislas, 1985;Tan, Shen, Wang, & Yu, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…Members of the Anacardiaceae family have been shown to contain derivatives of benzaldehyde and phenolic acids [2], [3], [4], and alkyl or alkylene derivatives of catechol, resorcinol, and phenol [5], [6], [7], [8]. Some of these natural products are reported to exhibit tyrosinase inhibitory [2], antibacterial and molluscicidal [3], IkBa kinase inhibitory [4], nematicidal [5], antithrombin [9], and antiplasmodial [10] properties.…”
mentioning
confidence: 99%
“…The present study reports the isolation of one oleaneane(1)and three lupane type triterpenoids (2-4), four anacardic acid[alk(en)yl-phenol] derivatives (5-8), and one flavone (9) for the first time from the root bark of O. insignis. Interestingly, compounds 1, 2 and 4 were characterized for the first time from the genus Ozoroa and have been isolated from the genus Rhus of the same family (Franke et al, 2001;Gu et al, 2007;Lee et al, 2005). This finding confirms that the genera Ozoroa and Rhus are closely related taxonomically.…”
Section: Chemotaxonomic Significancementioning
confidence: 99%